115 Effects of Probiotic and Heat-Killed Probiotic Supplementation on Systemic Biomarkers of Oxidative Stress and Inflammation and Fermentative end Products of Adult Cats. (21st September 2022) - de Souza, Sergio Miranda; He, Fei; de Godoy, Maria R; Davenport, Gary M
Abstract: Probiotics and heat-killed probiotics (postbiotic) have been linked with enhancement of the intestinal barrier function and mucosal immunity, anti-inflammatory properties, as well as production of fermentative end-products including short-chain fatty acids (SCFA), which may confer benefits to the gut microbiome and health. This study aimed to evaluate the longitudinal effects of daily supplementation of pro- and post-biotics on oxidative stress biomarkers such as malondialdehyde (MDA) and superoxide dismutase (SOD), inflammatory biomarkers from a panel of 19 cytokines and chemokines, the hormone leptin, as well as the fecal metabolites, such as phenol and indole, SCFA, and ammonia, of adult cats. The study was a complete randomized design with 36 cats divided into 3 treatments (n=12/treatment). Animals were fed a standard extruded commercial diet. The treatments used were control diet + placebo (maltodextrin carrier; CON), control diet + Probiotic (Bifidobacterium animalis subsp. Lactis CECT8145; daily dosage: 109CFU/cat; PRO), and control diet + postbiotic (Heat-killed Bifidobacterium animalis subsp. lactis CECT8145; daily dosage: 10 9 CFU/cat; PST). Test articles were supplied by ADM Biopolis (Valencia, Spain). Longitudinal analyses were performed every 30 days for a total of 90 days. No interaction of day by treatment (P >0.05) was observed for any of the variables evaluated. For fecal metabolites, there was a main effect of treatment for butyrate concentration, PST was greater (P< 0.05) than PRO. It was also observed a main effect of treatment for some cytokines and chemokines, cats on CON had reduced (P< 0.05) GM-CSF, KC, and SDF-1, when compared with PST, PRO, and both PST and PRO respectively. Whilst for RANTES and IL-12(p40), cats on CON had greater concentration (P< 0.05) when compared with cats on PST and PRO, and PST, respectively. Overall, the supplementation of the probiotic and postbiotic showed no detrimental effects on oxidative stress and inflammatory biomarkers, and fermentative end-products in adult cats.